The moderating effect of alternate Mediterranean diet on the association between sedentary behavior and insomnia in postmenopausal women - Sheng, Zhumei; Zhou, Mincong (Frontiers in Nutrition, 2025)
AimThe study aimed to explore the moderating role of the alternate Mediterranean diet (aMED) adherence on the association between sedentary behavior and insomnia symptoms in postmenopausal women.MethodsData regarding postmenopausal women were obtained for this cross-sectional study from the National Health and Nutrition Examination Survey (NHANES) 2005–2008. Sedentary behavior and insomnia symptoms were assessed using the questionnaire. aMED adherence was evaluated according to 24-h dietary recalls. Weighted univariate logistic regression models were utilized to screen potential covariates. The relationship between sedentary behavior, aMED adherence, and insomnia symptoms was explored using weighted univariate and multivariate logistic regression models. All results were expressed as odds ratios (ORs) and 95% confidence intervals (CIs).ResultsA total of 1,793 postmenopausal women were included in the final analysis. Of them, 643 (37.56%) reported experiencing insomnia symptoms. Among the postmenopausal women, sedentary time of >8 h was associated with insomnia symptoms (OR = 1.41, 95% CI = 1.01–1.96), prolonged nocturnal awakening (OR = 1.38, 95% CI = 1.06–1.79), and undesired early morning awakening (OR = 1.59, 95% CI = 1.09–2.30). No association was observed between adherence to the aMED and insomnia symptoms (OR = 1.05, 95% CI: 0.77–1.44). Among the postmenopausal women with lower adherence to the aMED, the odds of insomnia symptoms were higher in those with sedentary time ≥8 h (OR = 1.63, 95% CI: 1.02–2.62). Similarly, in the participants with low aMED adherence, sedentary time ≥8 h was also associated with prolonged nocturnal awakening (OR = 1.90, 95% CI = 1.27–2.83) and undesired early morning awakening (OR = 1.85, 95% CI = 1.09–3.16).ConclusionAdherence to the aMED modulates the association between sedentary behavior and insomnia symptoms in postmenopausal women. Interventions targeting sedentary behavior and dietary patterns may improve sleep quality and overall health in postmenopausal women.